Chef Minoritas di Tempat Kerja: Perempuan di Dapur Profesional - Septiani, Intan Yusan; Siscawati, Mia (UI Scholars Hub, 2022)
Cooking activities in the traditional kitchen or in the domestic area—which are supposed to be the domain of women—are interpreted as an obligation as well as a form of a woman’s service to her family, spouse, children, and even other people who are close to her life. In other words, cooking in the domestic area is an undefined job. Regardless of the fact, when cooking shifted to the public space, it turned into a professional job, a work area which was later known as the professional kitchen. People who work in a professional kitchen are given the title professional chef. Ironically, such a professional kitchen, often thought to be easily controlled by women—who for centuries have always been related to cooking activities—is actually controlled and dominated by men, starting from culinary studies (tata boga) to the industry. As a skill, cooking is actually an activity that can be performed by anyone, regardless of gender. In reality, cooking activities, in both traditional and professional kitchens, place women in a marginal and subordinate position. To learn why women, who are often considered as “the queen of the traditional kitchen”, find it difficult to control and dominate professional kitchens, we examine a number of studies that have analyzed the professional life of female chefs as well as various forms of gender inequality in the chefs’ workplace or the professional kitchen.